2003
DOI: 10.1007/s11664-003-0219-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of strain on abnormal grain growth in Cu thin films

Abstract: To understand a grain growth mechanism in Cu thin films that were deposited on rigid substrates by sputter deposition and subsequently annealed at various temperatures, microstructures of the Cu films with or without the rigid substrates were analyzed by x-ray diffraction (XRD), transmission electron microscopy (TEM), and electrical resistivity measurements. Significant grain growth (with bimodal grain size distribution) was observed during roomtemperature storage in the Cu films deposited on the Si 3 N 4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 14 publications
(19 reference statements)
0
27
0
Order By: Relevance
“…Although several parameters (such as surface energy, grain boundary energy, impurities, etc) to control the grain growth of the Cu thin films were proposed, [5][6][7][8] we demonstrated experimentally in our previous papers 9,10) that the strain (or stress) introduced into the thin films was the primary factor to enhance the grain growth specially at low temperatures in addition to surface/grain boundary energy.…”
Section: Introductionmentioning
confidence: 99%
“…Although several parameters (such as surface energy, grain boundary energy, impurities, etc) to control the grain growth of the Cu thin films were proposed, [5][6][7][8] we demonstrated experimentally in our previous papers 9,10) that the strain (or stress) introduced into the thin films was the primary factor to enhance the grain growth specially at low temperatures in addition to surface/grain boundary energy.…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2, the reduction of the values could be explained by the reduction of the grain-boundary density in the films due to grain growth, as observed previously. 20) Thus, the grain growth rate of the 6N-Cu film is smaller than that of the 4N-Cu film.…”
Section: Cu Films With Thickness Of 100 Nmmentioning
confidence: 97%
“…We concluded that the organic additives (needed for electroplating) were not the only primary factor causing Cu grain growth. 20) Because the Cu films have intrinsic strain when deposited on the rigid substrates, the strain introduced in individual grains of the Cu film was concluded to be the primary factor to induce abnormal grain growth. 20) Strain in the polycrystalline metal films is generally relaxed by several deformation (or strain relaxation) mechanisms, which are influenced by film microstructure and impurities in the films.…”
Section: Inrtoductionmentioning
confidence: 99%
See 2 more Smart Citations